(3GdHSW hGdJYQja aj fXe eG Ld ef GdJUQjas - (3CHhRjO YHO GdQMef Hf Ydj GdechOj GdaGSj,J (B807 (3g` s ((3eYGhjI Hf CMeO GdaGVd s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NhdfG fYeg hHGdMLG aVdfG hNUfG Hage CSdhH GdYQH fXekG hfKQkG hgh ef CSfi GdYQH hHYO aGdbUO HPG GdJUQja fXe bhGYO ef GdJUQja s
(3BNQgG (B:s
(3heG CQOfG LeYg bO cMdG Ydi aUhd LeI eTJedkG CHjGJg Ef cfJ YO eMUjg JSYg CHjGJ hGQHYeGFI ced HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eQbeI s
(3HBNQgG aGFOI s
(3cJHJ HYV cdeGJgG HGdMeQI hcPdc GdahGUd hYfGhjf GdCHhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs